Respon Pemberian Hormon 2,4-D dan BAP terhadap Pertumbuhan Subkultur Kalus Kedelai (Glycine max (L.) Merrill) secara In Vitro - Kiki Ayuningrum; Iman Budisantoso; Kamsinah Kamsinah (Fakultas Biologi | Universitas Jenderal Soedirman, 2015)
The purpose of this study was to evaluate the response of administration of a combination of 2,4-D and BAP on the growth of soybean callus subculture and determine the combination of 2,4-D and BAP most good for the growth of soybean callus subculture. The study design used completely randomized design (CRD) with a pattern factorials. The factor one e.i 2,4-D consists of 4 levels, namely: 0, 5, 10, and 15 ppm. A factor of 2 e.i BAP consists of 4 levels, namely: 0, 2, 4, dan 6 ppm. Every combination treatment repeated three times. Parameters measured include the percentage is growing callus, type of callus, dry weight and wet weight of soybean callus. The results showed that administration of the hormone 2,4-D and BAP can spur the growth of soybean callus subculture, the combination of BAP 2 ppm and 10 ppm of 2,4-D is the best combination for a percentage of callus and growing callus types, whereas the wet weight and the weight dried callus is not driven by a combination of the hormone 2,4-D and BAP